ANALISIS LITERASI KEUANGAN, PERILAKU KEUANGAN DAN PENDAPATAN TERHADAP KEPUTUSAN INVESTASI MAHASISWA DI KOTA BATAM - Siringo ringo, Juniarti; Banjarnahor, Haposan (SCIENTIA JOURNAL, 2023)
Human life will always be related to economic activities, because every human being often has various needsto continue life. To meet this need, humans need money as a means of meeting these needs. In meetingneeds, humans must use good financial planning so that every need can be achieved. In this planning can bedone such as preparing income and expenditure budgets, saving, investing, doing credit or insurance. Investingis one of the best ways to generate and store wealth over the long term. The purpose of this study was tomeasure and analyze the effect of financial literacy, financial behavior and income on the investment decisionsof students residing in Batam City. The author uses primary data, namely by distributing questionnaires using aLikert scale to obtain processed data. This writing provides a separate assessment or criteria for the object tobe studied (purposive sampling). The population in this study are active students who are in the accountingstudy program in Batam City. Meanwhile, the number of samples amounted to 100 respondents.